Programy społecznej odpowiedzialności biznesu jako element strategii przedsiębiorstwa - Bem, Kornelia (Annales. Etyka w Życiu Gospodarczym, 2008)
During the last several years we have witnessed heightened interest in the issue of CSR, which has been frequently raised at numerous conferences. In addition, a growing number of enterprises have become increasingly aware of the relevance of socially responsible actions and begun including them in the conducted business activity. CSR is gradually becoming an integral part of the company strategy. It is best demonstrated in companies with a large share of foreign capital, where Polish subsidiaries adopt patterns from the parent companies. In the first two parts, the paper outlines the programs of CSR, their key elements and premises, as well as introduces the importance of the company strategy. The final part attempts to convince the reader that along the development of the CSR concept, a gradual process of converting theory into practice is taking place. The CSR programs are becoming an important element of the business strategy. Companies, bigger ones in particular, have begun to take account of the strategies closely interlinked with the very CSR programs.